(untitled) (Journal of Dhaka Medical College, 2023)
Objective: This study is aimed to see the level of high sensitivity C-reactive protein (hs-CRP) and its association with manifestations of polycystic ovary syndrome (PCOS). Design: This cross-sectional study was conducted over a period of one year (January 2017 to December 2018) in the department of Endocrinology of a University hospital. Participants: Fifty-five PCOS patients diagnosed on basis of revised Rotterdam diagnostic criteria 2003 and 50 age-matched healthy controls [PCOS vs. Control- BMI (kg/m2): 25.47±4.65 vs. 20.68±3.51, p<0.001]. Main outcome measures: hs-CRP level, manifestations of PCOS Methods: After relevant history and physical examinations, blood was taken in fasting state during follicular phase of menstrual cycle to measure total testosterone (TT), luteinizing hormone (LH), follicle stimulating hormone (FSH) and hs-CRP. Hormones were measured by chemiluminescent microparticle immuno-assay and hs-CRP by nephelometric technique. Results: hs-CRP (mg/L) was found significantly higher in PCOS patients [1.67 (0.69, 2.54) vs. 0.94 (0.30, 1.42), p=0.006] even after adjustment for age and BMI [OR (95% CI): 1.585 (1.093, 2.299), p=0.015]. Also hs-CRP status (>5 mg/L) was found significantly higher in them than that of controls; but only in non-obese (BMI <25 kg/m2) participants [7.27% vs. 0.0%, p=0.018]. hs- CRP showed no significant correlation and predictive association with any of the manifestations of PCOS including age, BMI, waist circumference, TT and LH/FSH ratio [p=NS for all] Conclusions: Patients with PCOS had significantly higher hs-CRP level and high hs-CRP status without any significant association with its manifestations. J Dhaka Med Coll. 2021; 30(2) : 142-148